Analysis of Special Standardization of Accessible Toilet Facilities at Dharma Negara Alaya Arts Building, Denpasar, Bali - Trisnasari Subrata, Ni Putu Eka; Hendrawan, Freddy; Emmi Nutrisia Dewi, Ni Made; Algifari Hayatullah, Muhammad (Malikussaleh University, Aceh, Indonesia, 2025)
People with disabilities in Indonesia still often face limitations in accessing public facilities that meet their needs. This highlights the importance of providing disability support facilities that meet standards, especially in public spaces, for community interaction. One example of a public facility that accommodates the community is an art building, the Dharma Negara Alaya (DNA) Arts Building, located in Denpasar City, Bali Province. This study aims to analyze the standardization of supporting facilities for people with disabilities in the Dharma Negara Alaya Arts Building, focusing on accessible toilet facilities. The analysis was carried out based on the Regulation of the Minister of Public Works Number 30 of 2006, which regulates technical guidelines for facilities and accessibility in building structures and the environment. This study uses a descriptive qualitative approach through direct observation and interviews with building users to evaluate the adequacy and suitability of the design of accessible toilet facilities. The study results on the Implementation of accessible toilet facilities in the Alaya Building have followed the standards by the Regulation of the Minister of Public Works of 2006 concerning Guidelines for Technical Requirements for Buildings, and the availability of toilet facilities has been met. However, some design deficiencies still need to be fixed or improved, such as the use of door materials, the room size not yet optimal for standard movement, and no elbow ramps to help wheelchair users access. There are no sanitary facilities or special washbasins for people with disabilities. This research is expected to provide insight into fulfilling the needs of inclusive design for people with disabilities and provide recommendations for improving accessibility at the Dharma Negara Alaya Arts Building, especially for accessible toilet facilities.